Sebuah proses abusive relationship dalam hubungan berpacaran - Nisa, Icha Fitrian (Universitas Brawijaya, 2023)
A relationship (dating) that is established on the basis of affection between lovers, which involves various emotional feelings can in fact also have negative impacts such as abusive tendencies towards one another. Various forms of abuse (verbal, physical, sexual, and economic) received by the victim as well as the presence of various factors (comfort, length of relationship, fulfillment of affection needs, et cetera) can cause victims to persist in abusive relationships. This study aims to identify and understand the process of the occurrence of abusive relationships, using the research method of observational interviews or structured interviews and using qualitative analysis. The results showed that the four participants had experienced verbal abuse and two of them also experienced physical abuse. The conclusion of this study is that the four participants experienced the same abusive relationship process (5 stages), starting with the initial enjoyment stage until the end of the relationship. The implication of this research is that society can identify and be aware of the abusive relationship process in order to minimize the further impact of violence.